(untitled) (LACCEI, 2024)
Hypertension is a disease that causes many annual deaths worldwide, with greater affection in the elderly due to their little physical activity on a daily basis, in addition to being related to various diseases generated by obesity, as well as excessive consumption of alcohol and cigarettes, increasing the number of cases of patients with hypertension due to the confinement of COVID-19, that made people stay indoors without physical activity and increase the eating and sleeping habit, as well as the increase in sedentary lifestyle in patients with high blood pressure who can not perform any physical activity in an energetic way because it could cause death, according to the World Health Organization (WHO) is the fourth risk factor of annual deaths, being important to diagnose patients who are at risk of suffering hypertension to prevent them from acquiring any disorder in their health. In view of this problem, in this article a blood pressure measurement system was performed for the care of patients at risk of hypertension monitored by mobile application and to know the value of blood pressure on the walls of the arteries to determine if the patient has normal or elevated blood pressure. Through the development of the system, it was observed that it works in the best way and allowed us to obtain an efficiency of 98.47%, being an accepted value for performing the process quickly and accurately.